Avaliação morfológica da placenta do Holochilus scireus naturalmente infectado pelo Schistosoma mansoni - LEÔNCIO, Gabriel Gomes (2021)
Schistosomiasis is a parasitosis caused by the trematode Schistosoma mansoni. According to the Ministry of Health, the schistosomiasis in Maranhão is endemic in more than 20 municipalities. The transmission of this parasitosis occurs through contact with fresh water collections, contaminated by S. mansoni eggs, where intermediate hosts (snails of the genus Biomphalaria) are also present. In view of the similarity between the rodent placenta and the human (hemocorial discoid) placenta, combined with the lack of existing scientific literature, this study aimed to histologically characterize the rodent placenta Holochilus sp naturally infected by S. mansoni that inhabit the Baixada Maranhense. From September 20019 to March 2020, a total of 13 females of the species H. scireus were evaluated, of which 4 were in different stages of pregnancy. The rodents of the genus Holochilus sp found in the study were susceptible to infection by S. mansoni.